Imagining sisterhood in modern Chinese texts, 1890-1937 - Zhu, Yun 1979- (Lexington Books, 2017)
Through the lens of the discursive reconstruction and cultural reimagining of sisterhood, this book investigates the dynamic entanglements and contestations among women, nation, and Chinese modernity